Performance study of routing protocols for wireless sensor network applications - 1 - Heng, Tian Hao (2014)
The importance of Wireless Sensor Networks (WSN) has increased over the years with many applications developed in areas of healthcare monitoring, environment monitoring, and various applications in the military. However, WSN face problems in energy efficiency and data transmission, with the need of a reliable routing protocol that allows efficient routing of data packets from nodes to a sink.